2006
DOI: 10.1111/j.1439-0523.2006.01240.x
|View full text |Cite
|
Sign up to set email alerts
|

Transgressive segregation for reduced glucosinolate content in Brassica carinata A. Braun

Abstract: Successful commercial utilization of the meal by-product of Brassica oilseed crops requires the cultivation of cultivars with low glucosinolate (GSL) content in the seeds; however, such cultivars are not yet available in Brassica carinata. The objective of the present research was to search for transgressive segregants with further-reduced GSL content in the progeny of crosses involving four B. carinata lines with reduced GSL content (90 compared with 120 lmol/g seed in standard germplasm). The four lines were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Its ability to reduce summer weed species’ seed banks makes it suitable for integrated pest management in crop production systems [ 7 , 16 ]. Carinata also has potential as a feed crop (due to its high protein and low fiber content [ 17 19 ]) and biofumigant (varieties with high glucosinolate content [ 20 ]). There have been concerted efforts both from public and private entities in the last few years to establish carinata as a sustainable biofuel crop in the United States [ 1 , 16 , 21 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its ability to reduce summer weed species’ seed banks makes it suitable for integrated pest management in crop production systems [ 7 , 16 ]. Carinata also has potential as a feed crop (due to its high protein and low fiber content [ 17 19 ]) and biofumigant (varieties with high glucosinolate content [ 20 ]). There have been concerted efforts both from public and private entities in the last few years to establish carinata as a sustainable biofuel crop in the United States [ 1 , 16 , 21 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The task seems arduous, but it will only possible if approached through several strategies. Previous research conducted through intraspecific selection led to the development of a line with stable glucosinolate content of 52 micromoles g -1 seed (Márquez-Lema et al 2006). Recombination between that genetic source and the line BCH-1773 developed in the present research seems an attractive approach that might result in a further improvement of the trait.…”
Section: Discussionmentioning
confidence: 96%
“…Velasco et al (1999) reported the development of six lines with a slight reduced glucosinolate content (80-100 micromoles g -1 seed compared to 120 micromoles g -1 seed in the check). Crosses between these lines produced transgressive segregation from which a line with a glucosinolate content averaged over two environments of 52 micromoles g -1 seed, compared to 73 micromoles g -1 seed in the best parent, was isolated (Márquez-Lema et al 2006). The present research represents a further advance in the reduction of glucosinolate content in B. carinata.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breeding approaches are often employed to obtain crops with low GSL content for food or feed purposes [ 26 , 27 , 28 ], while those with high GSL content remain of interest for non-food applications. Therefore, the choice of species should be carefully considered with regard to the downstream purposes of raw materials.…”
Section: Natural Occurrence Of Glucosinolatesmentioning
confidence: 99%